The incidence, natural history, and predictive factors for tissue protrusion after drug‐eluting stent implantation. Issue 1 (17th February 2021) - Otagaki, Munemitsu; Fujii, Kenichi; Matsumura, Koichiro; Noda, Teppei; Shibutani, Hiroki; Hashimoto, Kenta; Morishita, Shun; Tsujimoto, Satoshi; Yamamoto, Yoshihiro; Park, Haengnam; Yoshioka, Kei; Shiojima, Ichiro
Abstract: Objectives and background: Although tissue protrusion (TP) between the stent struts after stent implantation has been implicate as a potential factor of stent failure, the incidence, natural history, and predictive factor of TP after stent implantation remains unclear. This prospective study evaluated the fate of TP after drug‐eluting stent (DES) deployment using optical coherence tomography (OCT). Method and result: This study analyzed TP for 42 lesions after DES in which three serial OCTs, including preprocedure, postprocedure, and 1‐month after the procedure were performed. TP was classified into the five groups: (a) persistent, (b) progressive, (c) healed, (d) regressive, and (e) late‐acquired. Immediately after the procedure, 100 TPs in 37 lesions (88%) were identified. Of those, 53 (53%) were persistent, 3 (3%) were progressive, 20 (20%) were healed, and 24 (24%) were regressed at 1‐month follow‐up. Seven TPs in five patients (13%) were observed only at 1‐month follow‐up (late‐acquired). Conclusion: In lesions with late‐acquired TP, calcified nodule was identified as an underlying plaque morphology on preprocedural OCT. A serial OCT analysis found TP occurred not only immediately after DES implantation, but also 1‐month after DES implantation.